ANALYSIS OF SOCIETY PARTICIPATION AND DESTINATION DEVELOPMENT IN TOURISM VILLAGES - Supriono, Supriono; Kurniawan, Andy; Nurrahma, Aisyah Asri (Profit: Jurnal Adminsitrasi Bisnis, 2022)
Malang Regency is an area in Indonesia with numerous capacities for tourism village. One of them is Gunungronggo Village. It has a lot of potential and attractions with the main tourist value namely the natural springs of Sumber Jenon. The study aimed to discuss the participation of local communities in Gunungronggo Village and its destination development. The analysis of study applied descriptive research methods and qualitative approaches. Methods of data collection were performed by observations, interviews with resource persons and documentation. The results of study showed that local residents’ participations were divided into two types. First, an active participation was carried out by local communities who managed tourism, and people who sold food and drinks around destinations. Then, a passive participation referred to people who only took orders from their superiors and formed their participation by not doing activities which damaged the environment. Meanwhile, the development of destinations in Gunungronggo Village included five components. They were attractions, accessibility, amenities, ancillary services, and institutions.